A decade of 10-valent pneumococcal conjugate vaccine use in Lithuania: trends in invasive pneumococcal serotype dynamics - Petrutienė, Aurelija; Sinotova, Jekaterina; Pupienienė, Nijolė; Marcinonytė, Raminta; Padvilikytė, Indrė; Razmuk, Jelena; Muralytė, Svajūnė; Bulavaitė, Aistė; Plečkaitytė, Milda (Frontiers in Public Health, 2025)
BackgroundStreptococcus pneumoniae causes invasive pneumococcal disease (IPD), a serious condition characterized by the spread of pneumococci to normally sterile human body sites. Pneumococcal conjugate vaccines (PCVs) have reduced IPD incidence caused by vaccine serotypes, though non-vaccine serotypes remain a risk. Lithuania introduced the 10-valent PCV (PCV10) into the National Immunization Program in 2014, with a subsequent switch to PCV15 in 2024. This study aimed to assess the impact of PCV10 on the distribution of invasive serotypes across the population and age groups over a decade of vaccine implementation.Materials and methodsA total of 1,190 invasive pneumococcal isolates collected during the pre-PCV10 (2010–2014) and post-PCV10 (2015–2024) periods were stored at the National Public Health Surveillance Laboratory and routinely serotyped using the Quellung reaction and multiplex PCR. We analyzed serotype distribution in the overall population and separately in children and adults, with the adult group further stratified into 18–64 and ≥65 years.ResultsThe number of invasive pneumococcal isolates significantly exceeded the annually reported IPD cases, indicating substantial underreporting in Lithuania. The proportion of PCV10 serotypes declined significantly in the overall population, decreasing from 50% in 2010–2014 to 20% in 2024 (p = 0.00002) and within age-specific groups. Non-PCV10 serotypes, primarily 19A (p = 0.0015), 3 (p = 0.004), and 6C (p = 0.0061), and serotypes 8 and 22F, showed increasing trends. Serotype 3 has remained the most prevalent IPD serotype since 2015. From 2018 onward, serotype 19A became the second most common serotype among adults aged 18–64 years, while its increase among children was less apparent, likely due to the low number of pediatric isolates.ConclusionThis is the first study in Lithuania to demonstrate that the childhood vaccination program reduced IPD caused by vaccine serotypes in children and unvaccinated adults through indirect protection. However, serotype replacement following PCV10 introduction likely contributed to the observed increase in non-vaccine serotype IPD cases among adults. Limitations in current IPD surveillance hinder the ability of Lithuanian health authorities to make timely, evidence-based decisions regarding the impact of PCVs. Strengthening surveillance systems is essential to inform and guide effective pneumococcal vaccination strategies.